2014
DOI: 10.1371/journal.pone.0097897
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Therapeutic Potential of a Nitrosylating Agent in the Treatment of Ovarian Cancer

Abstract: This study examines the role of s-nitrosylation in the growth of ovarian cancer using cell culture based and in vivo approaches. Using the nitrosylating agent, S-nitrosoglutathione (GSNO), a physiological nitric oxide molecule, we show that GSNO treatment inhibited proliferation of chemoresponsive and chemoresistant ovarian cancer cell lines (A2780, C200, SKVO3, ID8, OVCAR3, OVCAR4, OVCAR5, OVCAR7, OVCAR8, OVCAR10, PE01 and PE04) in a dose dependent manner. GSNO treatment abrogated growth factor (HB-EGF) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…In addition, we have also recently reported that STAT3 activation induced by IL-6 is inhibited by endogenously generated nitric oxide (NO) from inducible NO synthase (iNOS) or exogenously supplemented GSNO via S-nitrosylation of Cysteine 259 residue of STAT3 molecule, documenting that STAT3 S-nitrosylation is a physiological regulation [14] . We have also reported that inhibition of STAT3 by GSNO is implicated in TH17 immunomodulation under EAE conditions [15] and anti-proliferation of microglia and cancer cells [16,17] . GSNO is an endogenous NO carrier which plays a crucial role in redox based nitrosylation of protein thiols (S-nitrosylation) in health and disease [18] and is now recognized as an important cell signaling mechanism [19] .…”
Section: Introductionmentioning
confidence: 81%
“…In addition, we have also recently reported that STAT3 activation induced by IL-6 is inhibited by endogenously generated nitric oxide (NO) from inducible NO synthase (iNOS) or exogenously supplemented GSNO via S-nitrosylation of Cysteine 259 residue of STAT3 molecule, documenting that STAT3 S-nitrosylation is a physiological regulation [14] . We have also reported that inhibition of STAT3 by GSNO is implicated in TH17 immunomodulation under EAE conditions [15] and anti-proliferation of microglia and cancer cells [16,17] . GSNO is an endogenous NO carrier which plays a crucial role in redox based nitrosylation of protein thiols (S-nitrosylation) in health and disease [18] and is now recognized as an important cell signaling mechanism [19] .…”
Section: Introductionmentioning
confidence: 81%
“…Recently our laboratory and others reported that GSNO inhibited growth of head and neck squamous carcinoma and ovarian cancer via inhibition of STAT3 and NF-κB activities [15, 55]. GSNO is the most abundant endogenous small molecular mass S-nitrosothiol in mammalian cells and widely used as an S-nitrosothiol donor in many experimental setups.…”
Section: Discussionmentioning
confidence: 99%
“…GSNO could activate PI3K/Akt pathway in relatively low concentration [39], but inhibit the pathway in high concentration [40]. We found that Akt phosphorylation did exist in cardiac differentiation course of ES cells, and peaked at day 5 EB stage (Fig.…”
Section: Gsno Promotes Cardiomyogenesis Via H 2 O 2 -Dependent Pi3k/amentioning
confidence: 66%